Weed Survey on Wheat in the Northern State, Sudan - Mohamed, Mukhtar Abdel Aziz (University of Khartoum Journal of Agricultural Sciences, 2023)
A weed survey was conducted in seven locations in Dongola area during the winter season of 2008/2009 to determine the most prevalent weed species associated with wheat (Triticum aestivum L.). A stratified random sampling procedure was adopted and each location was divided into fields, of which 10 were randomly selected. Number of individual weed species was determined in 10 quadrates, each 1 m 2 . The field density, field frequency, field uniformity, relative field density, relative field frequency, relative field uniformity and relative abundance of the species were determined. The data revealed the presence of 29 species of annual and perennial weeds belonging to 15 families. The highest number of species occurred in Elmasakeen and Sheikh Shareef, while the lowest was recorded in Selaim basin. Sinapis arvensis, Cynodon dactylon, Malva palviflora, Convolvulus arvensis, Chenopodium album and Sorghum arundinaceum occurred at high relative abundance. Species with moderate relative abundance were Cyperus rotundus, Trigonella hamosa, Eruca sativa, Chenopodium murale and Sinapis alba. The other species occurred in few locations and exhibited low to very low relative abundance